2021
DOI: 10.3389/fbioe.2020.613771
|View full text |Cite
|
Sign up to set email alerts
|

PCR & Go: A Pre-installed Expression Chassis for Facile Integration of Multi-Gene Biosynthetic Pathways

Abstract: The introduction of multi-gene metabolic pathways is generally the first step for the construction of microbial cell factories and plays an essential role in metabolic engineering and synthetic biology. Here, we developed a “PCR & Go” system for facile integration and assembly of multi-gene pathways into the chromosome of Saccharomyces cerevisiae. The core component of the “PCR & Go” system was an expression chassis, where eight promoter/terminator pairs were pre-installed into the yeast chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Nevertheless, more studies should be performed in near future to further improve the multigene pathway integration platform. For example, similar to previous studies (Qi et al, 2020; Reider Apel et al, 2017), we found that the expression level of the same expression cassette was dependent on the integration sites. The detailed mechanisms on such a context‐dependent gene expression level (X. Chen & Zhang, 2016) are yet to be explored.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, more studies should be performed in near future to further improve the multigene pathway integration platform. For example, similar to previous studies (Qi et al, 2020; Reider Apel et al, 2017), we found that the expression level of the same expression cassette was dependent on the integration sites. The detailed mechanisms on such a context‐dependent gene expression level (X. Chen & Zhang, 2016) are yet to be explored.…”
Section: Discussionsupporting
confidence: 91%
“…S1 . Genome integration loci and the corresponding gRNA plasmids (Supplementary Table S2 ) were constructed in our previous studies 29 , 36 38 . For the construction of strains VSY001-VSY024, target gene expression cassettes were amplified by PCR with 40 bp homology arms to the target chromosomal loci and co-transformed with the corresponding gRNA plasmids to the Cas9 expressing yeast strains using the LiAc/SS carrier DNA/PEG method 39 .…”
Section: Methodsmentioning
confidence: 99%
“…In another study, Qi et al utilized the highly efficient genomic loci from Apel et al and built a yeast strain containing eight well-defined cassettes in eight different loci ( Apel et al, 2017 ; Qi et al, 2021 ). Each cassette contained a unique set of promoters and terminators with a synthetic linker in the middle, resulting in a strain with eight promoter-linker-terminator cassettes in the genome ( Figure 5C ).…”
Section: Crispr/cas9 Multiplex Gene Editingmentioning
confidence: 99%
“…However, because the Cas9 cassette, promoters, and terminators were pre-integrated into the genome, the transformation only required plasmid(s) with gRNA cassettes and donor DNA genes (without promoters and terminators). This platform successfully integrated five genes in the astaxanthin biosynthetic pathway into five different loci with 69% efficiency ( Qi et al, 2021 ).…”
Section: Crispr/cas9 Multiplex Gene Editingmentioning
confidence: 99%
See 1 more Smart Citation